Surveying Hong Kong in the 1950s: Western humanitarians and the 'problem' of Chinese refugees. (25th November 2014) - MADOKORO, LAURA
Abstract: At the end of the Second World War, there were over a million displaced persons and refugees in Europe alone. Hundreds of thousands of people were uprooted with the expansion of the Japanese empire across the Pacific Theater, and many others were similarly displaced when Japan was defeated. Others later fled civil conflicts, in South Asia, for instance, and in China, where thousands left the mainland during the final days of the Chinese Civil War. Among this massive displacement in Asia, unlike in Europe, only a few groups were identified as refugees. One such group consisted of the migrants in Hong Kong who, after 1949, were understood to be refugees fleeing communist oppression in the People's Republic of China. This article examines the critical role that surveys (population studies designed to account for, and define, refugee groups) played in shaping particular, Westernized Cold War understandings of the refugee experience in Hong Kong. These surveys were organized by non-state interests and undertaken with financial support from major American philanthropies. In examining the objectives and methodologies of the refugee surveys conducted in Hong Kong in the early 1950s, in contrast with studies undertaken contemporaneously in Europe, this article observes that, although at the time the flaws in the surveys were recognized and regularly disregarded in the pursuit of broad political objectives, scholars have failed to adequately recognize the subjective nature of the surveys' supposedly empirical evidence. As a result, the dominant European-based narrative about modern refugees has obfuscated the distinctive aspects of the refugee experience in Hong Kong.